The regulatory influence of the visual system: an exploratory study in gymnastics vaulting - Haigis, T.; Schlegel, K. (Science of Gymnastics Journal, 2020)
Approach runs in order to maximize approach velocity are an inherent component in many sports. The goal of the study was to investigate the regulation of a complex motor task in gymnastics vaulting and the impact of the visual system within these processes. It was hypothesized that a visual perception-based strategy incorporating time-to-contact information derived from the variable tau is used to optimize the run-up in particular. Kinematic parameters of 10 gymnasts performing handsprings were examined. The analysis revealed that, on average, onset of visual control took place three steps prior to the hurdle. Linear regression showed that tau margin is dependent on the velocity of the approach run. The study supports the idea of a regulation of the run-up that is based on a visual strategy in which the influence of the vaulting table is crucial. The gymnasts were able to adapt the step length and duration respective to the movement velocity in order to facilitate an optimal transition of the run-up towards the take-off board and subsequent the vaulting table. In the process the influence of run-up velocity relating to the value of tau at the onset of visual control is of utmost importance.